Analysis of Employee Performance Quality Improvement at PT. Pos Indonesia (Persero) Gunungsitoli Branch - Krisfan Hermansyah Mendrofa; Meiman Hidayat Waruwu (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This research aims to analyze the improvement of employee performance quality at the Office of PT. Pos Indonesia (Persero) Gunungsitoli Branch. The problems underlying this research are the persistence of employee indiscipline in complying with working hours, delays in data entry for goods, and performance inconsistencies that negatively affect service quality to customers. This research uses a qualitative descriptive method with data collection techniques through observation, in-depth interviews, and documentation. Informants consist of one key informant, namely the Executive Manager, and two supporting informants, namely the Process Supervisor and the UPL Services and Audit Supervisor. The research findings show that the employee performance quality improvement program has been implemented through performance target-setting, routine briefings and evaluations, supervisory oversight, internal audits, and the enforcement of Standard Operating Procedures (SOP). Employee performance quality is generally at a fairly good level, though not yet fully consistent, particularly during periods of increased workload volume. The implementation of these programs has had a positive impact on operational stability, inter-unit coordination, and the formation of a more disciplined and accountable work culture. The sustainability of performance improvement requires the strengthening of a measurable indicator-based evaluation system and continuous employee competency development